A novel sensor based on bead-counting of purple sweet potato tapioca pearl for freshness monitoring of shrimp. (30th January 2022) - Wangmo, Lungten; Suratsawadee, Atitaya; Ratvijitvech, Thanchanok; Siripinyanond, Atitaya
Graphical abstract: Highlights: Purple sweet potato (PSP) tapioca pearl as a colorimetric pH sensor was developed. The change in color of the PSP tapioca pearl correlated with the change in pH of beverages. PSP tapioca pearl was sensitive to ammonia and pH changes. Various tapioca pearls stacked in a pipette tip was used as a distance based colorimetric sensor. The bead counting concept was used to monitor the freshness of shrimp. Abstract: A novel sensor based on bead-counting of purple sweet potato tapioca pearl for freshness monitoring of shrimp was proposed. The sensor was prepared from commercially available tapioca pearls with purple sweet potato as a natural colorant by using a similar procedure as to prepare "Thai Saku dessert". A novel concept of using five tapioca pearls stacked in a pipette tip was proposed to observe the color change of the pearls by bead counting approach. The color of the tapioca pearl changed from purple to greenish-blue upon the detection of volatile amines and then to green on prolonged exposure to volatile amines. This color change was observed from the first bead and gradually observed on the next beads according to the concept of distance-based colorimetric measurement. This work is the first to demonstrate the use of bead counting as a novel, low-cost sensor technology for estimating the freshness of shrimp.